THE EFFECT OF GOOD CORPORATE GOVERNANCE ON CORPORATE VALUES ON COMPANIES LISTED IN JAKARTA ISLAMIC INDEX - eliya dwi nurianti (State Islamic Institute (IAIN) Tulungagung, 2020)
The purpose of this research is to determine the effect of Good Corporate Governance on Company Value in Companies Listed in the Jakarta Islamic Index 2016-2018. Used independent variables namely institutional ownership, independent commissioners and audit committees. While the dependent variable is the value of the company. This type of research is quantitative. The sampling technique used purposive sampling, and the type of data is secondary data. The data analysis techniques used are normality test, classic assumption test, multiple linear regression test and hypothesis test. This type of research is quantitative. The sampling technique used purposive sampling, and the type of data is secondary data. The data analysis techniques used are normality test, classic assumption test, multiple linear regression test and hypothesis test. Based on the results of the analysis it can be concluded that partially institutional ownership has a negative and significant effect on the value of the company, independent commissioners have a positive and significant effect on the value of the company and the audit committee has a negative and no significant effect on the value of the company in companies listed in JII in 2016-2018. While simultaneously institutional ownership variables, independent commissioners and audit committees have a significant effect on firm value